Competitividad sistémica en Lázaro Cárdenas: el aporte del puerto - Rangel Hernández, Eduardo (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
It is certain that nowadays the trade at international level is one of the main bonds among the nations, it is one of the activities with bigger growth and expansion in the last years, phenomenon of which the countries cannot be to the margin, under this situation one of the most important means that contributes to the increment from the commercial relationships to world level is the marine ports that are used in function of their characteristics of geographical localization and infrastructure in connection with the tendencies of the international trade, what allows him/her to be competitive in front of other ports. For the above-mentioned we can identify that the port of Lázaro Cárdenas presents certain factors associated to his trade, services, equipment, works, areas and infrastructure that allow him/her to offer favorable conditions for the development of the trade so much national as international, besides a strategic location and some social factors that facilitate his growth taking advantage

Es indudable que hoy en día el comercio a nivel internacional es uno de los principales vínculos entre las naciones, es una de las actividades con mayor crecimiento y expansión en los últimos años, fenómeno del cual los países no pueden quedar al margen, bajo esta situación uno de los medios más importantes que contribuye al incremento de las relaciones comerciales a nivel mundial son los puertos marítimos, que son utilizados en función de sus características de localización geográfica e infraestructura en relación con las tendencias del comercio internacional, lo que le permite ser competitivos frente a otros puertos. Por lo anterior podemos identificar que el puerto de Lázaro Cárdenas presenta ciertos factores asociados a su comercio, servicios, equipamiento, obras, áreas e infraestructura que le permiten ofrecer condiciones favorables para el desarrollo del comercio tanto nacional como internacional, además de aprovechar una ubicación estratégica y algunos factores sociales que facilitan su crecimiento.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2006-0003; Comercio internacional; Competitividad sistémica; Sector portuario; Capital logístico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/900